Investigating Literary Terminologies to Accomplish Literary Research and Enjoyment: A Corpus Study - Agista Nidya Wardani; Adityo Adityo (STKIP Singkawang, 2021)
In relation to producing, enjoying, and especially criticizing literature, some literary terminologies are used frequently. Thus, corpus in the field of Literature is urgently needed to compile. This study aims to compile literary terminologies found in Literature and Language Teaching by Gillian Lazar and Literary Movements for Students by Ira Mark Milne books. In addition, it also tries to find the frequency, meaning (in context), and examples of the use of the terminologies. The method used in this research was document analysis, the data of which was obtained from predetermined documents, such as books of general literature, and books of theory and literary criticism. While the stages carried out were data collection, data selection, and presentation. From the books studied, it is found that the terminologies that appear could be categorized into terminologies related to (1) authors, (2) readers of literary works, (3) literary work itself, and (4) literary theory and criticism. Additionally, there is an interesting fact from the data found that the books have different frequencies of literary terminologies. The terminologies that appeared in Literary Movements for Students are more frequent.